Suprasellar mature teratoma: case report - Guk, Mykola O.; Danevych, Olena O.; Chukov, Andriy A.; Zemskova, Oksana V.; Chuvashova, Olga Y.; Iegorova, Katerina S.; Ukrainets, Oleksii V.; Kulichenko, Alina Y.; Tsiurupa, Dmytro M.; Shmelyova, Anna A. (Ukrainian Neurosurgical Journal, 2021)
Intracranial teratomas are tumors that occur mainly in childhood and extremely rare in adulthood. They account up to 50% congenital CNS tumors. In this article a case of mature teratoma in 33 year-old female patient with progressive visual impairment is presented. Differential diagnosis at preoperative stage was difficult. Outcome analysis of neuroimaging study method and clinical picture provided evidence of epidermal cyst. Transnasal endoscopic approach as a treatment method was chosen, but during the surgery the atypical tissue for epidermal cyst was identified with tight adhesion to the right internal carotid artery which limited the extent of surgical tretment. Pathohistological and immune histochemical study detected mature teratoma. Detailed visual impairment dynamic and instrumental methods of diagnosis during postoperative supervision are presented in the article. The choice of management, namely, surgical intervention using extended endoscopic transnasal approach is considered to be controversial and risky among different authors taking into account intraoperative characteristics of this tumor.